Introduction and review of services of contemporary Sindhi scholars of Shah Waliullah Muhaddith Dehlvi: شاہ ولی اللہ محدث دہلوی کے ہم عصر سندھی علماء کا تعارف اور خدمات کا جائزہ - Channar , Dr. Mehmood ul Hassan; Khoso, Professor Dr. Aijaz Ali; Mahar, Moulana Muhammad Ahmed (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Shah Waliullah Muhaddith Dehlvi contributions to Islamic scholarship are indeed significant, and his relationship with Sindh and its scholars presents a rich field for research. The article aims to introduce contemporary Sindhi scholars who were active during Shah Waliullah time, emphasizing their parallel efforts in promoting Tafsir, Hadith, and Jurisprudence. Both Shah Waliullah and these Sindhi scholars played crucial roles in disseminating knowledge and advocating for Tawheed and Sunnah in their respective regions. This mutual influence and shared objectives underscore the importance of regional scholarship in the broader context of Islamic education and thought. This topic not only enriches the understanding of Shah Waliullah’s legacy but also sheds light on the interconnectedness of Muslim scholars across different regions during that period. It opens avenues for further research into how these interactions shaped Islamic teachings in South Asia.